Generalized Derivations on Prime Rings with Involution - Alahmadi, Adel; Alhazmi, Husain; Ali, Shakir; Khan, Abdul Nadim (Communications in Mathematics and Applications, 2017)
Let \(R\) be an associative ring. An additive mapping \(F : R → R\) is called a generalized derivation with an associated derivation \(d\) of \(R\) if it satisfies \(F(xy) = F(x)y + xd(y)\) for all \(x, y \in R\). In the present paper, we obtain description of the structure of \(R\) and information about the generalized derivation \(F\) which satisfies certain \(*\)-differential identities on prime rings with involution.